2011
DOI: 10.1007/s12253-010-9352-9
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Hormones and Signaling Molecules in Describing the Relationship Between Obesity and Colon cancer

Abstract: Colon cancer represents a highly prevalent disease in the Western world. While dietary and lifestyle recommendations remain important factors in disease prevention and treatment, epidemiological data have made it clear that obesity and excess body weight remain significant risk factors for the disease. A number of potential direct and indirect relationships exist between obesity and increased risk of colon cancer. Several mechanisms which appear promising and warrant further investigation are discussed here, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 71 publications
0
24
0
Order By: Relevance
“…Although numerous adipokines have been identified, only a few have been extensively studied for their involvement in promoting or inhibiting colon cancer tumor growth. These include leptin, resistin, adiponectin, and others (38). Elevated levels of circulating leptin have been shown to increase the risk of colon cancer (37) and other malignancies.…”
Section: Adipose Tissue and Adipocytes In Obese Individuals Support Tmentioning
confidence: 99%
“…Although numerous adipokines have been identified, only a few have been extensively studied for their involvement in promoting or inhibiting colon cancer tumor growth. These include leptin, resistin, adiponectin, and others (38). Elevated levels of circulating leptin have been shown to increase the risk of colon cancer (37) and other malignancies.…”
Section: Adipose Tissue and Adipocytes In Obese Individuals Support Tmentioning
confidence: 99%
“…Even though the mechanisms remain not completely clarified, there is convincing evidence from epidemiological and experimental studies that dietary factors are likely to have a major influence on the risk of several types of cancer, particularly of the GI tract [93,94,95,96,97]. In vivo experiments using mice showed that diet-induced obesity increases risk of colonic cancer while a signaling/modular implication of leptin (both a hormone and a cytokine) was also suggested by the data [96,97].…”
Section: The Role Of Dietary Berries In Various Types Of Cancermentioning
confidence: 99%
“…The loss of the sensitivity of cells to insulin is associated with changes in the signaling of chemokines, cytokines, growth hormones, and steroid hormones [8890]. This may explain why metabolic disease goes along with an increased risk of certain cancers, for example, breast and colon cancer.…”
Section: Enzymes In the Sulfatase Pathway In Estrogen-associated Cmentioning
confidence: 99%